Temporal trends in quality of primary care for patients with type 2 diabetes mellitus: A population‐based retrospective cohort study after implementation of a quality improvement initiative. Issue 2 (16th October 2017) - Wong, Carlos K.H.; Fung, Colman S.C.; Yu, Esther Y.T.; Wan, Eric Y.F.; Chan, Anca K.C.; Lam, Cindy L.K.
Abstract: Background: This study examined whether temporal trends exist in treatment of patients with type 2 diabetes (T2D) and quality of diabetes care after implementation of quality improvement initiative in primary care setting. Methods: We conducted a population‐based retrospective cohort study of 202, 284 patients with T2D who were routinely managed in primary care clinics. We examined the change over time and the variability between clinics in quality of care from Hospital Authority administrative data over a 5‐year period (2009‐2013) and used multilevel logistic regression to adjust for patient and clinic characteristics. Observational period was partitioned in 5 calendar years. Ten quality‐of‐care criteria were selected: adherence to 7 process of care criteria (HbA1c test, renal function test, full lipid profile, urine protein analysis, retinal screening, lipid‐lowering agent prescriptions among patients with hypercholesterolaemia, and angiotensin converting enzyme inhibitor/angiotensin receptor blocker prescriptions among patients with microalbuminuria) and 3 outcome of care criteria (HbA1c ≤ 7%, BP ≤ 130/80 mmHg, and LDL‐C ≤ 2.6 mmol/L). Variability of standards between clinics was assessed by using intracluster correlation coefficients. Results: Characteristics of patients with T2D managed in primary care changed substantially during the observational period, with increasing age and usage of insulin and longer duration of diabetes but improved metabolic profiles (all P trend < .001). Performance rates of the 7 process and 3 clinical outcomes of care criteria increased remarkably over time (all P trend < .001). Variations in retinal screening delivery between clinics were considerable, albeit decreasing over time. Conclusions: Coinciding with implementation of quality improvement initiative, quality of diabetes care improved significantly in the past 5 years, in part attributable to benefits of integrated multidisciplinary diabetes management.